Evaluation of Bus Rapid Transit Stop Design Against Universal Design Criteria in Bandar Lampung City - Sari, Intan Mustika; Murwadi, Haris (Jurnal Arsitektur, 2025)
Since its construction in 2011, BRT stops in Bandar Lampung have been spread along the Rajabasa-Sukaraja and UNILA-ITERA routes, with the last renovation in 2019. However, after the pandemic, its function changed to become a place for street vendors to trade and a place for the homeless to rest. The BRT system requires ramp stairs that can reduce delays, especially for the elderly, disabled, and passengers with luggage. This study identifies the typology of BRT stop designs, identifies the fulfillment of universal design standards, and determines the dominant variables that affect the quality of the stops. Using a qualitative descriptive method, 5 typologies were found from 41 existing stops. Dominant variables such as pedestrian lane width and stop capacity showed good results, but important variables such as guideways, stop ramps, and information boards did not meet universal standards. Overall, the level of fulfillment of universal design standards is in the "moderate" category with an index of 1-2. It is recommended that design improvements refer to stops with the highest index, such as Trans ITERA, to meet user needs according to universal design.